The effect of a coach motivational micro-climate intervention in swimming: a mixed-method evaluation - Moulds, K.; Abbott, S.; Cobley, S. (Frontiers in Psychology, 2026)
Theoretically informed by bio-ecological theory, research on coach-created motivational climates, and concerns regarding youth sport dropout in swimming, this study aimed to (1) develop and implement a motivational climate coach intervention for swimming coach development; and (2) evaluate intervention effects via swimmer and coach mixed-methods assessment. A quasi-experimental, repeated-measures, mixed-methods intervention was implemented over a 12-week period. Accredited Australian swimming coaches (N=19) from 19 clubs participated, with coaches alternately allocated into intervention or control groups. To determine pre-post intervention effects, affiliated swimmers (n=112 intervention; n=97 control)—not informed of coach grouping—completed the Empowering and Disempowering Motivational Climate Questionnaire (EDMCQ-C) at two timepoints (pre- and post-intervention follow-up). Meanwhile, coaches self-evaluated their coaching behaviours using the EDMCQ at similar time points. Findings indicated that, relative to controls, swimmers connected with intervention coaches reported higher empowering and lower disempowering coaching behaviours post-intervention, after adjusting for baseline ratings, with medium effect sizes. A greater empowerment gain was apparent among swimmers who rated their coach lower at baseline. Contrastingly, no pre-post changes were apparent in coach self-ratings. Qualitative interviews with intervention coaches identified perceived intervention benefits (e.g., communication styles) and impact on coaching behaviours. Findings suggested that coach motivational climate training could benefit knowledge and behavioural strategies for improving the youth sport experience and identified future research recommendations. Whether improved coaching climates can translate into broader impact on youth sport outcomes remains uncertain.